PEMBUATAN HAND SANITIZER DI UMKM RM MAMA RIRIE SAMARINDA: The Production of Hand Sanitizer at UMKM Mama Ririe Samarinda - Mubarok, Ahmad; Putri, Sri Astika (Program Studi Sastra Indonesia Universitas Mulawarman, 2022)
Abstract: In the current era of the Covid-19 pandemic, maintaining health and continuing to implement health protocols is very important. One effort that can be done is to clean hands using soap. However, this becomes inefficient when you are outside the home or when you have to travel. To overcome this, use hand sanitizer. The KKN activities that took place during the pandemic period encouraged students to carry out the hand sanitizer program at RM Mama Ririe KKN location. Hand sanitizer is a material that contains an antiseptic that is practical to use. To make a hand sanitizer, you need 95% alcohol, 3% HO, 98% glycerin and water. The resulting hand sanitizer has an alcohol content of 79%, which is in accordance with good antiseptic standards, namely the alcohol content ranges from 60-80%. So that, the hand sanitizer that has been made is safe to use and effective in killing germs on the hands. Keywords: alcohol; Covid-19, hand sanitizer. Abstrak: Di era pandemik Covid-19 saat ini, menjaga kesehatan dan terus menjalankan protokol kesehatan sangatlah penting. Salah satu upaya yang dapat dilakukan adalah dengan membersihkan tangan menggunakan sabun. Namun, hal tersebut menjadi tidak efisien dilakukan ketika berada di luar rumah atau saat harus bepergian. Untuk mengatasi hal tersebut digunakan hand sanitizer. Kegiatan KKN yang berlangsung selama masa pandemi mendorong mahasiswa untuk melakukan program hand sanitizer di lokasi KKN RM Mama Ririe. Hand sanitizer merupakan bahan yang mengandung antiseptik yang praktis untuk digunakan. Untuk membuat hand sanitizer diperlukan alkohol 95%, HO 3%, gliserin 98% dan air. Hand sanitizer yang dihasilkan memiliki kandungan alkohol sebesar 79%, di mana hal ini sesuai dengan standar antiseptik yang baik yaitu kandungan alkohol berkisar antara 60-80 %. Sehingga hand sanitizer yang telah dibuat aman untuk digunakan dan efektif untuk membunuh kuman pada tangan. Kata Kunci: alkohol; Covid-19; hand sanitizer.